2009
DOI: 10.1177/1078390308330050
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Quitlines and Persons With Mental Illnesses: Perspective, Practice, and Direction

Abstract: The prevalence of tobacco use among persons with mental illnesses is 2 to 3 times that of the general population, and these individuals suffer significant related health disparities. Many people with mental illnesses contact tobacco quitlines for cessation assistance. With free telephone counseling and in some cases nicotine replacement therapy, quitlines offer a potentially effective resource for this population. However, quitlines are still trying to determine how best to meet these callers' unique needs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Another study found that self-reported, 7-day point prevalence tobacco abstinence at 6 months among persons with mental illnesses equaled the overall quit www.annualreviews.org • Confronting a Neglected Epidemicrate (48). A randomized study of persons treated in public mental health systems showed that quitline counseling plus nicotine replacement therapy led to a significant reduction in selfreported number of cigarettes smoked per day (80). Unpublished data from the California Helpline reveal similar results.…”
Section: How Well Do Telephone Quitlines Work For These Populations?supporting
confidence: 65%
See 2 more Smart Citations
“…Another study found that self-reported, 7-day point prevalence tobacco abstinence at 6 months among persons with mental illnesses equaled the overall quit www.annualreviews.org • Confronting a Neglected Epidemicrate (48). A randomized study of persons treated in public mental health systems showed that quitline counseling plus nicotine replacement therapy led to a significant reduction in selfreported number of cigarettes smoked per day (80). Unpublished data from the California Helpline reveal similar results.…”
Section: How Well Do Telephone Quitlines Work For These Populations?supporting
confidence: 65%
“…Also, quitline staff work more effectively with persons with diagnosed-and undiagnosedbehavioral health issues after receiving training on behavioral health issues (80). Though quitlines appear to be one cost-effective cessation strategy for this population, unfortunately, far too few smokers avail themselves of this free service (37).…”
Section: How Well Do Telephone Quitlines Work For These Populations?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many mental health patients have also received messages from their providers that using tobacco is a relatively minor problem and that smoking cigarettes is actually beneficial to their mental health due to the temporary symptom reduction that psychiatric patients experience during smoking. A study by Morris et al (2009) found that most mental health providers receive little or no training on smoking cessation, and frequently have misconceptions such as the ideas that persons with mental illnesses need to smoke to control their psychiatric symptoms and that these individuals have no desire to quit.…”
Section: Stigma and Provider Beliefsmentioning
confidence: 97%
“…In the long term, tobacco use also adversely affects the user's personal income. Research has shown that over their lifetime, people with mental illnesses who smoke will spend up to one-third of their income on tobacco (Morris et al, 2009). …”
Section: Tobacco Related Morbidity Mortality and Functional Impactmentioning
confidence: 98%